Board Characteristics and Earnings Management - Mardianto, Mardianto; Dwiyanti, Windy (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
The purpose of this study is to examine the impact on earnings management as the dependent variable of board size, board independence, frequency of board meetings, board expertise, audit committee size, independence, frequency of audit committee meetings, and audit committee skills in finance and accounting. This research method is quantitative. This study uses time series data. The sample of this research is the financial statements from 2018 to 2022, which covers more than one period. The population of this study is non-financial sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period, with the sampling technique using purposive sampling method. The results showed that the independence of the board of directors, the frequency of board meetings, the independence of the audit committee, and the frequency of audit committee meetings had a significant positive effect on earnings management. Meanwhile, board size, board expertise, audit committee size, and audit committee skills in finance and accounting do not show a significant relationship with earnings management.